The role of polymorphisms of thiopurine methyltransferase in therapy with Azathioprine: preliminary study - Francesca Mortillaro; Carmelo Fabiano; Maria Piccione; Marco Giammanco; Fabio Venturella (Journal of Biological Research, 2018)
Azathioprine is an immunosuppressant drug belonging to the class of thiopurines widely used in clinical therapy. Its immunosuppressive action is linked to the substantial action mechanism in the inhibition of the synthesis of nitrogenous bases purine carried out in T-lymphocyte. The level of such medication limit resides in side effects such as myelosuppression and the development of tumours. The occurrence of side effects is linked to the presence of genetic polymorphisms of Thiopurine methyltransferase (TPMT). To date, 40 allelic variants for TPMT have been detected. However, those responsible for the reduction of enzyme activity are three: *2, *3A, *3C. The presence of one of the three polymorphisms makes the enzyme susceptible to degradation at proteasome level, and exposes the patient to high levels of the active drug that increases the probability of an occurrence of its side effects. Therefore, the Food and Drug Administration imposed the execution of a genetic test of TPMT typing in order to determine if the drug therapy is appropriate to the metabolic characteristics of the patient. The study had the aim of identifying the prevalence of the three aforementioned polymorphisms related to TPMT in a sample population in Palermo, Italy, highlighting the differences related to the sex of the patient and highlighting the main phenotypes. The results showed prevalence in the population of the absence of polymorphism. Among the most frequent polymorphisms is the *3A (3%). A percentage of 1.5% was found for the polymorphism *3C. No polymorphism *2 was identified in the population analyzed.